FLT-3 Ligand in combination with bovine Granulocyte-Macrophage colony-stimulating factor and interleukin-4, promotes the growth of bovine bone marrow derived dendritic cells - Hope, J.C.; Werling, R.A.; Collins, R.A.; Mertens, B.; Howard, C.J. (Wiley, 2000)
Culture of bone marrow precursor cells with cytokines, including granulocyte - macrophage colony-stimulating factor (GM-CSF), interleukin-4 (IL-4) and the tyrosine kinase receptor binding proteins Flt-3 ligand (Flt3L) and stem-cell factor (SCF), has previously been shown, in both mouse and human, to result in the ,generation of large numbers of dendritic cells. We extend these findings to bovine dendritic cells. Culture of bovine bone marrow cells with GM-CSF, IL-4 and either Flt-3L or SCF - enhanced the generation of low buoyant-density dendritic cells. However, only the addition of Flt-3L to cells cultured with GM-CSI= and IL-4 was shown to increase the number of dendritic cells and induce the differentiation of dendritic cells with potent capacity to stimulate allogeneic T cells and resting CD4+ memory T cells. The effective ability to stimulate T cells was associated with the expression of major histocompatibility complex (MHC) class II molecules and CDSO/86 by dendritic cells. Bovine bone marrow derived dendritic cells appeared to be exclusively of myeloid origin because they expressed the myeloid-related antigens CD 14, MyD-1 and CD 1 lb.